Long-term ultrasonographic changes of the canine prostate gland after castration - Spada, Stefano; De Felice, Daniela; Arlt, Sebastian; Aires, Luiz Paulo Nogueira; England, Gary C. W.; Russo, Marco (Frontiers in Veterinary Science, 2025)
IntroductionUltrasound imaging (US) is the method of choice to assess the canine prostate gland. Whilst recent studies have documented the role of castration in the development of prostatic neoplasia, little is known about parenchymal and perfusion features of the normal and abnormal prostate in neutered dogs. No data are available concerning prostatic changes after the first 90 days following castration. The present study aimed to acquire data on the long-term ultrasonographic changes occurring to the canine prostate after castration.Materials and methodsTen adult neutered dogs underwent B-mode US and contrast-enhanced ultrasound (CEUS) of the prostate on two occasions: day of the first examination (T0) and six years later (T1). The prostate was evaluated via B-mode US and the volume was calculated using Atalan’s formula. For CEUS examination, an intravenous contrast agent (SonoVue) was administered to assess prostatic perfusion. Videoclips were recorded, and time-intensity curves were obtained to determine contrast parameters: peak enhancement (PPI) and time to peak (TTP). Volumetric and perfusion results were then compared between timepoints.ResultsAt both examinations, the prostate appeared similar on B-mode US in terms of morphology and echotexture, minimally decreasing in volume over time. Prostate perfusion was significantly reduced in all dogs between T0 and T1, with a PPI decrease from 54.9 to 29.6% and an increase in TTP from 26.3 to 47 s.DiscussionThese preliminary data provide baseline information on the B-mode appearance and CEUS measurements of the prostate gland of neutered dogs and suggest that prostatic involution after castration is not a short-term process but continues over several months.